The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/een.12421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dung beetle species richness and chemical perturbation on multiple ecosystem functions

Abstract: 1. The relationship between biodiversity and ecosystem functioning is typically positive but saturating, suggesting widespread functional redundancy within ecological communities. However, theory predicts that apparent redundancy can be reduced or removed when systems are perturbed, or when multifunctionality (the simultaneous delivery of multiple functions) is considered.2. We used manipulative experiments to test whether higher levels of dung beetle species richness enhanced individual functions and multifun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 62 publications
4
23
0
1
Order By: Relevance
“…Some important factors influencing the rate of dung removal could be recognized, although the highest explanatory capacities corresponded to the combined effects of several types of variables, where the three types of variables exercise a joint and indivisible effect on dung removal (fastest under summer conditions with high temperatures and assemblages with a high biomass). In experimental as well as field studies, dung beetle diversity is identified as a key factor in explaining ecological functions, such as dung removal or soil perturbation (Rosenlew & Roslin, ; Beynon et al., ; Braga et al., ; Manning et al., ). In our study, the main predictor was the total volume, represented by dung beetles collected in the traps in which dung removal was measured (TIE traps).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some important factors influencing the rate of dung removal could be recognized, although the highest explanatory capacities corresponded to the combined effects of several types of variables, where the three types of variables exercise a joint and indivisible effect on dung removal (fastest under summer conditions with high temperatures and assemblages with a high biomass). In experimental as well as field studies, dung beetle diversity is identified as a key factor in explaining ecological functions, such as dung removal or soil perturbation (Rosenlew & Roslin, ; Beynon et al., ; Braga et al., ; Manning et al., ). In our study, the main predictor was the total volume, represented by dung beetles collected in the traps in which dung removal was measured (TIE traps).…”
Section: Discussionmentioning
confidence: 99%
“…Most literature about dung beetle removal is focused on experimental or mesocosmos designs. Several studies have estimated dung removal efficiency and other ecological functions according to the (low) number, identity, and functional characteristics of selected species (Horgan, ; Finn & Giller, ; Slade et al., ; Rosenlew & Roslin, ; Nervo et al., , ; Tixier et al., ; Yoshihara & Sato, ; Manning et al., ). However, aside the importance of dung removal to understand nutrient cycling and ecosystem functioning, not many studies have directly estimated dung removal in field samples (Holter, ; Lee & Wall, ), and only few have done this under neotropical forest conditions (Herrick & Lal, ; Andresen, ; Amézquita & Favila, ; Braga et al., ; Batilani‐Filho & Hernández, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although limited in factors such as scale/replication, time frame, geographic range and dung beetle species, our results add to the literature showing that there are important ecosystem service benefits from dung beetles (e.g. Slade et al ., ; Beynon et al ., ; Manning et al ., ; Manning et al ., ; Piccini et al ., ). These findings are relevant both to agricultural systems where native dung beetle faunas are at risk from intensification of agriculture (Hutton & Giller, ) or systems where there are naturally impoverished dung beetle faunas, with active release programmes aiming to increase species richness (Edwards, ; Forgie et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…If an entire country has a naturally impoverished pastoral dung beetle fauna, then many species of dung beetle may require to be introduced to achieve improvements in ecosystem services over seasons and in pastures that will vary in factors such as farming types, soils, or climates (Tyndale-Biscoe, 1994;Edwards, 2009). Furthermore, evidence suggests that more diverse dung beetle communities can provide better benefits to ecosystem services than comparatively species-poor communities, but that species composition effects can be complex and warrant further study (Slade et al, 2007;Beynon et al, 2015;Manning et al, 2016;Manning et al, 2017;Piccini et al, 2017;Slade et al, 2017).…”
Section: Conclusion and Caveatsmentioning
confidence: 99%
“…A relatively small sample size, and variability in remaining dung mass (likely caused by the colonization of soil fauna) meant that we could not make any meaningful post-hoc corrections for differences in dung quality. More precise estimates of dung removal, including use of dry mass (Manning et al , 2017), or loss-on-ignition (Menéndez et al , 2016), would permit better tests of whether dung decomposition is impaired by anthelmintic residues, but either approach is destructive and would not allow us to make long-term estimates. Despite variability in initial dung conditions, we found that dung was fully degraded the following spring, regardless of the addition of beetles or the presence of moxidectin residues.…”
Section: Discussionmentioning
confidence: 99%